LIGHT LEPTOQUARKS AND HIGGS PAIR PRODUCTION - Enkhbat, Ts (Proceedings of the Mongolian Academy of Sciences (Online), 2016)
The data collected by the LHC experiments at 7 and 8 TeV with ~5 and 20fb-1 respectively is refining the details of the Higgs like resonances found last year [1,2]. Many decay channels have been searched for and the individual channels so far have given us a consistent picture with what one expects from the SM Higgs. On the other hand, the self interaction of the Higgs, which is probed by the Higgs pair production [3-7], is too feeble in the SM to be detected with these early data set. Even at 14 TeV run, the luminosity required for probing this process is very high [7-17]. This fact, namely the smallness of the corresponding Higgs pair production cross-section, makes it sensitive to a presence of a new physics [18-31]. In particular, relatively light colored particles are known to affect the cross-section substantially [18-22]. As a mater of fact there are many models with various motivations including models of GUT remnants [32-39], composite models [40-48] or a radiative neutrino mass models [49-51] which may give such contributions. Among these the scalars are interesting as they may play crucial role in the spontaneous symmetry breaking through additional terms with large portal couplings in the scalar potential. In the present work we study the phenomenological consequences of the Standard Model extension by two or more colored scalar particles. As a case study we take several leptoquarks (LQ) since there is an active experimental program by both ATLAS and CMS [52-57] and the lower bounds on their masses have now reached impressive levels some as high as a TeV value. On the other hand simultaneous presence of several LQs, may open up additional channels and therefore weakens these bounds. Specific models where the LQs are introduced to explain a certain phenomenon usually requires more than one LQs as in the model we study here. I examine a possibility of the existence of LQs with masses as light as ~180 GeV and study their effect for the single and di Higgs productions. As we will see the Higgs pair production is substantially altered in the low mass range below 300 GeV without too much change in the Higss diphoton decay channel if portal couplings are large. These couplings are required to have opposite signs by the latest Higgs data or small in magnitude. The model I consider has two LQs, an SU(2) doublet ω and a singlet χ. As we will see their simultaneous presence still allows them to have relatively light masses and escape the current bounds. In particular, the current bounds do not include LQs decaying to τt the masses below 200 GeV. Such a scenario, for example, has appeared in a model considered by Babu and Julio [49], where the light neutrino masses are induced by two-loop effects from LQs. If their masses are only of order few hundred GeV, as it is required in this case, the scenario can be probed or even excluded with the data from the LHC. Therefore this is one of the easiest model which can be tested and is the subject of the current study. Although I consider a particular model, it should be stressed that other models with colored particles can affect the pair productions in a similar manner.In Section II, I briefly list the current experimental status on the Higgs production and decay rates. Then I introduce the model I examined in the paper. Section III contains main part of this work where the numerical results for the single and pair Higgs productions are presented. The conclusion is given in Section IV.